PELATIHAN ADMINISTRASI KEPENDUDUKAN BAGI KETUA RW DAN RT DI KELURAHAN MEKARMULYA KECAMATAN PANYILEUKAN BANDUNG - Lestari, Sri; Eko Ginanjar, Sunandie; Sari, Elen; Dwiyono Amir, Hendy (ABISATYA DINAMIKA ISWARA PUBLISHING, 2022)
Abstract Service is the main means for creating comfort for the community, one of which is in administrative management. Community Service Activities carried out by the PKM STIA Bagasasi Team aim to produce outputs of increasing service capabilities to the community, especially for 37 RT and 6 RW heads in the Kelurahan Mekarmulya, Kecamatan Panyileukan, Kota Bandung. The management of the RT and RW which just ended in May 2022 and was replaced by a new management, made the public service of population administration experienced a few obstacles, so PKM activities were held to provide knowledge and understanding of population administration service standards, the development of the administrative management process as well as how to review the progress of the administration being processed. The result of this activity is the increasing knowledge and understanding of the community through the heads of RW and RT regarding population administration and improving services to the community.